Hippocampal lesions produce both nongraded and temporally graded retrograde amnesia in the same rat. Issue 5 (12th February 2013) - Winocur, Gordon; Sekeres, Melanie J.; Binns, Malcolm A.; Moscovitch, Morris
Abstract Rats were administered contextual fear conditioning and trained on a water‐maze, spatial memory task 28 days or 24 h before undergoing hippocampal lesion or control surgery. When tested postoperatively on both tasks, rats with hippocampal lesions exhibited retrograde amnesia for spatial memory at both delays but temporally graded retrograde amnesia for the contextual fear response. In demonstrating both types of retrograde amnesia in the same animals, the results parallel similar observations in human amnesics with hippocampal damage and provide compelling evidence that the nature of the task and the type of information being accessed are crucial factors in determining the pattern of retrograde memory loss associated with hippocampal damage. The results are interpreted as consistent with our transformation hypothesis (Winocur et al. (2010a) Neuropsychologia 48:2339–2356; Winocur and Moscovitch (2011) J Int Neuropsychol Soc 17:766–780) and at variance with standard consolidation theory and other theoretical models of memory. © 2013 Wiley Periodicals, Inc.